2020
DOI: 10.1212/nxi.0000000000000856
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognostic value of longitudinal measurements of blood neurofilament levels

Abstract: ObjectiveTo assess the long-term prognostic value of an integral of longitudinal measurements of plasma neurofilament light chain levels (NfLlong) over 12 and 24 months vs single neurofilament light chain (NfL) measurements in patients with relapsing-remitting MS (RRMS) and its additional value when combined with clinical and MRI measures.MethodsThis analysis included continuously fingolimod-treated patients with RRMS from the 24-month FTY720 Research Evaluating Effects of Daily Oral therapy in Multiple Sclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
5
17
1
Order By: Relevance
“…Meanwhile, we measured serum biomarkers by MSD other than SIMOA which previous study always applied. Although the concentration of serum biomarkers included NfL and cytokines/chemokines detected in our study was tend to be consistent with that detected by SIMOA in other studies (16,39,41,42), prospective studies are warranted to confirm the current findings.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, we measured serum biomarkers by MSD other than SIMOA which previous study always applied. Although the concentration of serum biomarkers included NfL and cytokines/chemokines detected in our study was tend to be consistent with that detected by SIMOA in other studies (16,39,41,42), prospective studies are warranted to confirm the current findings.…”
Section: Discussionsupporting
confidence: 91%
“…A composite model including bNfL and T2 lesion load was, therefore, deemed robust for predicting long term disability ( Chitnis et al, 2018 ). A similar conclusion was reached by Häring et al (2020) and Bittner et al (2020) , who measured bNfL and MRI lesion load in 814 individuals with CIS or newly diagnosed MS from 22 centers across Germany.…”
Section: Correlation Of Nfl Levels With Radiological and Clinical Finsupporting
confidence: 70%
“…Axonal damage resulting in brain volume loss plays a key role in long term disability ( Furby et al, 2008 ; Domingues et al, 2019 ; Marciniewicz et al, 2019 ). As expected, bNfL levels have been used as potential predictors of long-term progression according to the Expanded Disability Status Scale (EDSS; Häring et al, 2020 ), however, findings are inconsistent. A study that included 607 individuals with MS followed up for 12 years, showed a significant increase of 80% in bNfL levels per increase in EDSS score ( Cantó et al, 2019 ).…”
Section: Correlation Of Nfl Levels With Radiological and Clinical Finmentioning
confidence: 85%
See 1 more Smart Citation
“…Although it is not in the scope of this review, the increasing interest in neurofilaments and markers of neuroinflammation as biomarkers in both AD and PD, needs also to be mentioned. Neurofilament has been identified as a marker of disease progression or prognostic marker in several neurological conditions from multiple sclerosis [ 107 ] to amyotrophic lateral sclerosis [ 108 ] and, importantly also in both AD [ 109 ] and PD [ 110 ]. A major breakthrough in the research of this biomarker has been the demonstration that its levels in plasma significantly correlate with those in the CSF [ 111 ], making it a much more accessible biomarker.…”
Section: Other Biomarkers In Ad and Pd Researchmentioning
confidence: 99%